Transpacific studies : framing an emerging field - Hoskins, Janet; Nguyen, Viet Thanh, 1971- (Intersections (Honolulu, Hawaii), 2014)
Proposes a framework for transpacific studies that examines the flows of culture, capital, ideas, and labor across the Pacific. These flows involve Asia, the Americas, and the Pacific Islands. The introduction to the anthology by its editors, Janet Hoskins and Viet Thanh Nguyen, consider the advantages and limitations of models found in Asian studies, American studies, and Asian American studies for dealing with these flows. The editors argue that transpacific studies can draw from all three in order to provide a critical model for considering the geopolitical struggle over the Pacific, with its attendant possibilities for inequality and exploitation. "Transpacific studies" also sheds light on the cultural and political movements, artistic works, and ideas that have arisen to contest state, corporate, and military ambitions.